1996
DOI: 10.1051/aas:1996244
|View full text |Cite
|
Sign up to set email alerts
|

Be stars in open clusters. I. uvby $ ^{\bf \beta}$ photometry

Abstract: Abstract. -We present uvbyβ photometry for Be stars in eight open clusters and two OB associations. It is shown that Be stars occupy anomalous positions in the photometric diagrams, which can be explained in terms of the circumstellar continuum radiation contribution to the photometric indices. In the (b − y)0 − MV plane Be stars appear redder than the non emission B stars, due to the additional reddening caused by the hydrogen free-bound and free-free recombination in the circumstellar envelope. In the c0 − M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 31 publications
4
20
0
Order By: Relevance
“…I present in Figure 3 two examples of Ha profiles with obvious variability of its emission with orbital phase. Fabregat et al (1996) determined the physical characteristics of the star and found that it is possible to conclude that neither component of the pair reaches the Terminal Age Main Sequence (TAMS). Nevertheless, BD56° 578 is still too poorly studied to make any final conclusion on its evolutional status.…”
Section: Be Stars In Double Systems With Both Components On the Main mentioning
confidence: 99%
“…I present in Figure 3 two examples of Ha profiles with obvious variability of its emission with orbital phase. Fabregat et al (1996) determined the physical characteristics of the star and found that it is possible to conclude that neither component of the pair reaches the Terminal Age Main Sequence (TAMS). Nevertheless, BD56° 578 is still too poorly studied to make any final conclusion on its evolutional status.…”
Section: Be Stars In Double Systems With Both Components On the Main mentioning
confidence: 99%
“…We note that the variable component of the BD enters the Strömgren photometric filter u (or U filter of the UBV system), which can then produce photometric indices that do not reflect the genuine photospheric BD of the star and leads to wrong spectral classifications, as well as to bad fundamental parameter determinations (Divan & Zorec 1982). The effects of circumstellar emission in the bands and indices of the Strömgren system have been studied in detail by Fabregat & Reglero (1990) and Fabregat et al (1996). They clearly show that circumstellar emission or absorption significantly modify the values of the (b − y) and c 1 indices, which cannot be considered as effective temperature indicators without applying the adequate corrections.…”
Section: Discussionmentioning
confidence: 86%
“…The large absorption in the south-east part has been previously pointed out by Waelkens et al (1990) from photoelectric photometry in the Geneva system, but surprisingly has not been accounted for in recent CCD studies. On the other hand, the low reddening value in the western part was already noted by Fabregat et al (1996). They considered the Be stars Oo 146, 245 and 566 as probable nonmembers, due to their reddening values (E(b − y) = 0.313, 0.346 and 0.308 respectively), which are much lower than the cluster average reddening.…”
Section: Reddening Intrinsic Colours and Distancementioning
confidence: 87%
“…If we assume that (b − y) 0 is a good temperature indicator for all luminosity classes (see below), this implies that the The case is much the same as for classical Be stars. Be stars also have continuum emission or absorption of circumstellar origin at the Balmer discontinuity, and hence their c 0 indices are anomalous (Fabregat et al 1996, and references therein). For comparison, in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation